Perversion and the social relation - Rothenberg, Molly Anne 1952-; Foster, Dennis A.; Žižek, Slavoj (Sic, 2003)
Beneath the skin : perversion and social analysis / Molly Anne Rothenberg and Dennis Foster -- Fatal west : W.S. Burroughs's perverse destiny / Dennis Foster -- Perversion / Bruce Fink -- "I know well, but all the same--" / Octave Mannoni -- Exotic rituals and family values in exotica / Nina Schwartz -- The ambiguity of the masochist social link / Slavoj Žižek -- Confessions of a medieval sodomite / James Penney -- "As if set free into another land" : homosexuality, rebellion and community in William Styron's The confessions of Nat Turner / Michael P. Bibler -- Contamination's germinations / E.L. McCallum